2009
DOI: 10.1103/physrevb.80.115109
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-selective Mott transitions in a doped two-band Hubbard model

Abstract: We extend previous studies on orbital-selective Mott transitions in the paramagnetic state of the half-filled degenerate two-band Hubbard model to the general doped case, using a high-precision quantum Monte Carlo dynamical mean-field theory solver. For sufficiently strong interactions, orbital-selective Mott transitions as a function of total band filling are clearly visible in the band-specific fillings, quasiparticle weights, double occupancies, and spectra. The results are contrasted with those of single-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…When the low-lying e g orbital (e.g., the x 2 − y 2 in the case of Mn1) on a Mn site becomes half-filled, strong electronic correlations drive an orbital-selective metal-to-insulator transition, with the opening of a Mott gap. Such an orbitalselective Mott transition has been reported before for the Hubbard model, originating from different bandwidth (or correlations) for different orbitals, [56][57][58][59][60][61] or due to the band degeneracy lifting, 62 as well as for materials. [63][64][65] The charge disproportionation between Mn 3+ and Mn 4+ also results in a strong site-selective character of the transition.…”
supporting
confidence: 54%
“…When the low-lying e g orbital (e.g., the x 2 − y 2 in the case of Mn1) on a Mn site becomes half-filled, strong electronic correlations drive an orbital-selective metal-to-insulator transition, with the opening of a Mott gap. Such an orbitalselective Mott transition has been reported before for the Hubbard model, originating from different bandwidth (or correlations) for different orbitals, [56][57][58][59][60][61] or due to the band degeneracy lifting, 62 as well as for materials. [63][64][65] The charge disproportionation between Mn 3+ and Mn 4+ also results in a strong site-selective character of the transition.…”
supporting
confidence: 54%
“…A few of many-body approaches have been employed to study the paramagnetic Mott transition, such as dynamic mean field theory (DMFT) [1][2][3][4][5][6][7][8] and Kotliar-Ruckenstein slave-boson method 9,10 , etc. With the slave spin technique, Yu and Si recently showed that a paramagnetic orbital insulating phase can exist when the Hund's coupling approaches zero 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Mott-Hubbard metal-insulator transitions (MIT) in multiorbital Hubbard models have been extensively studied since there are rich phase diagrams [1][2][3][4][5][6][7][8][9][10][11][12] . A few of many-body approaches have been employed to study the paramagnetic Mott transition, such as dynamic mean field theory (DMFT) [1][2][3][4][5][6][7][8] and Kotliar-Ruckenstein slave-boson method 9,10 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Classic Mott systems such as VO 2 and NiO contain several d-orbitals that are singly occupied. At present, although there are some studies on Mott transitions in multiorbital systems using dynamical mean-field theory (DMFT) 6,[8][9][10][11] , there is no formalism that describes the spectral weight rearrangements in such systems under doping nor any experiments that observe this effect. In particular, since DMFT neglects the momentum-dependence in the single particle selfenergy, the essential physics of hopping-induced spectral weight transfer under the introduction of dopings can not be captured correctly.…”
mentioning
confidence: 99%